Polanyi and Political Consumption: A Modern Theoretical Application of the Double Movement - Frank, Phillip M. (Society for Marketing Advances Proceedings, 2016)
There has been an increase in literature on a growing field recently termed, "Political Consumption" (Baumann et al., 2015). Political consumption is defined as the choice or avoidance of products or brands with the aim of changing ethically or politically objectionable institutional or market practices (Shah et al., 2007). The following paper posits a theoretical model for the conceptualization of political consumption. Specifically, the author presents Karl Polanyi and his "Double Movement" as the underpinning theoretical conceptualization of Political consumption. The author also proposes empirical research to test such a theoretical model.
Keywords: brand choice; branding (Marketing); consumer behavior; consumption (economics); double movement; political consumption; product management

Economic Exchange: Interdisciplinary Conceptualizations for Management Applications - Das, Roshni (Vilakshan: The XIMB Journal of Management, 2016)
The concept of 'Economic Exchange', taken in the neoclassical economics sense, has traditionally yielded a unilateral direction for business and management studies, that of profit maximization. This paper argues that, the same, when conceptualized from a sociological and anthropological point of view in particular, taking theorization by Polanyi (1946), Weber (1978) and Zafirovski (2001) into cognizance, can generate many alternative and interesting directions. Illustrations for the same have been provided in the form of management applications. Some controversies in the lifecycle of the concept have been noted such as that of the 'rational' man or Homo Economicus, which eventually led to the emergence of socio-economics and the consequential paradigmatic realignments among scholars, as a rebuttal to the dominant paradox. We undertake a conceptual exploration and synthesis of the relevant trans-disciplinary literature. Future implications for discursive research in management are discussed.
Keywords: WEBER, Max, 1864-1920; ZAFIROVSKI, M.; anthropology; economic exchange; economic man; homo economics; homo economicus; industrial management; methodological indivisualism; profit maximization; socioeconomics

Re-embedding Financial Stakes within Ethical and Social Values in Socially Responsible Investing (SRI) - Revelli, Christophe (Research in International Business and Finance, 2016)
The aim of this study is to understand how the definition of ethics in finance has steered socially responsible investing (SRI) towards a financial approach where ethics is guided by finance. Following a critical perspective of historical and modern SRI, we advocate a reconceptualization of the SRI paradigm through a framework that re-embeds finance in ethical and social values according to Polanyi's theory of embeddedness. To conclude, we propose an SRI model where impact measurement and extra-financial performance guide investments.
Keywords: economic anthropology; economic sociology; embeddedness; general financial markets: general (includes measurement and data) G10; social and economic stratification; social finance; socially responsible investing

Quality Work and the Moral Economy of European Employment Policy - Bolton, Sharon; Laaser, Knut; Mcguire, Darren (JCMS: Journal of Common Market Studies, 2016)
Following a decade of radical economic and workplace restructuring, it is important to understand how state employment policies support or deny human flourishing. This article utilizes a realist document analysis approach and reviews European employment policy through a moral economy lens. It fuses different moral economy approaches, drawing together the work of Karl Polanyi and Andrew Sayer a multi-layered conceptual lens is offered that explores the tensions between a commodification of labour and human needs. A dominant market ideology is revealed, highlighting how quality work has been subsumed by the flexicurity agenda in the EU.
Keywords: European employment policy; dignity; employment; flexicurity; management studies; moral economy; quality work